2021
DOI: 10.1097/md.0000000000026103
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of microRNA-367 in the clinicopathologic features and prognosis of breast cancer patients

Abstract: Breast cancer (BC) is a malignant tumor originating from cells of the breast. Notably, microRNAs have been recognized as biomarkers of BC metastasis. The present study is designed to evaluate the association between microRNA (miR)-367 expression and BC with the variance of clinicopathologic features and prognosis. Initially, 63 BC patients were allocated in the BC group, while the other 40 healthy volunteers were recruited as the control group. miR-367 expression in the serum of patients and healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The results of the study demonstrated that low expression of miR-367-3p was associated with positive ALNM, larger tumor size and a more advanced tumor-node-metastasis stage (30). In addition, a study conducted by Liu et al (31) revealed a strong association between miR-367 expression and the clinicopathologic features and prognosis of breast cancer. It was found that the miR-367 expression level in the serum of patients with breast cancer was significantly lower than that of the control group.…”
Section: Roles Of Mir-367 In Disease Pathogenesismentioning
confidence: 79%
See 2 more Smart Citations
“…The results of the study demonstrated that low expression of miR-367-3p was associated with positive ALNM, larger tumor size and a more advanced tumor-node-metastasis stage (30). In addition, a study conducted by Liu et al (31) revealed a strong association between miR-367 expression and the clinicopathologic features and prognosis of breast cancer. It was found that the miR-367 expression level in the serum of patients with breast cancer was significantly lower than that of the control group.…”
Section: Roles Of Mir-367 In Disease Pathogenesismentioning
confidence: 79%
“…Extensive cancer research has focused on miR-367, which has demonstrated tumor-suppressing activity through the targeting of oncogenes. In multiple types of cancer, including breast (30)(31)(32), gastric (33,34) and prostate cancer (35), higher levels of miR-367 have been associated with improved prognoses and survival rates. In addition, miR-367 has been recognized as a possible biomarker for diagnosing various types of cancer including breast (30,31) and gastric (33) cancer (Fig.…”
Section: Roles Of Mir-367 In Disease Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Differentially expressed miRNA may be used as the indicator of early diagnosis, molecular typing and prognosis, including ovarian cancer. [5][6][7] microRNA (miR-126), originally identified as an endothelial-specific miRNA playing an essential role in angiogenesis and vascular integrity, [8,9] it has been shown to function as a critical tumor suppressor in various types of solid tumors. [10][11][12][13] Overexpressed miR-126 can inhibit drug resistance cell proliferation and promote apoptosis of drug resistance cell, and invasion of cancer cells in various types of solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Differentially expressed miRNA may be used as the indicator of early diagnosis, molecular typing and prognosis, including ovarian cancer. [5–7] microRNA (miR-126), originally identified as an endothelial-specific miRNA playing an essential role in angiogenesis and vascular integrity, [8,9] it has been shown to function as a critical tumor suppressor in various types of solid tumors. [10–13]…”
Section: Introductionmentioning
confidence: 99%